2018
DOI: 10.1063/1.5049568
|View full text |Cite
|
Sign up to set email alerts
|

Using the second virial coefficient as physical criterion to map the hard-sphere potential onto a continuous potential

Abstract: In the same sense as in the extended law of corresponding states [M. Noro and D. Frenkel, J. Chem. Phys. 113, 2941 (2000)], we propose the use of the second virial coefficient to map the hard-sphere potential onto a continuous potential. We show that this criterion provides accurate results when the continuous potential is used, for example, in computer simulations to reproduce the physical properties of systems with hard-core interactions. We also demonstrate that this route is straightforwardly applicable to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 22 publications
2
20
0
Order By: Relevance
“…After equilibration, the thermostat was switched off, velocities were reinitialized, and the simulation was continued in the microcanonical ensemble, running for 10 4 τ with an integration step size of 2 × 10 −4 τ . As a check, we have confirmed that the simulations accurately reproduce the deviations from the Carnahan-Starling equation of state reported in [9]. For both methods, each simulation contained N = 15 3 = 3375 particles, and results were averaged over ten independent simulations.…”
supporting
confidence: 62%
See 2 more Smart Citations
“…After equilibration, the thermostat was switched off, velocities were reinitialized, and the simulation was continued in the microcanonical ensemble, running for 10 4 τ with an integration step size of 2 × 10 −4 τ . As a check, we have confirmed that the simulations accurately reproduce the deviations from the Carnahan-Starling equation of state reported in [9]. For both methods, each simulation contained N = 15 3 = 3375 particles, and results were averaged over ten independent simulations.…”
supporting
confidence: 62%
“…In particular, we simulate true hard spheres using event-driven molecular dynamics simulations using the approach of Alder et al [3]. The code used is an adaptation of the one in [4], modified to periodically output the stress tensor integrated over a short time interval (using equation (9) in [3]). Simulations were run for 7.5 × 10 4 τ after equilibration, with τ = √ βmσ 2 the time unit.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…A continuous potential has been proposed using a physical criterion based on the extended law of corresponding states [79] and the Mie potential [73] Baéz et al mapped the HS potential to a continuous function [80]. This equivalent function is referred as pseudo hard-sphere (PHS) and has been used to successfully reproduce thermodynamic properties of the HS fluid in a wide range of volume fractions [80]. Here, we use the PHS pair potential to straightforwardly determine the force between HS particles in a standard MD algorithm.…”
Section: Introductionmentioning
confidence: 99%
“…In the case of spherical particles, Medina-Noyola and coworkers demonstrated that structural properties and diffusion coefficients of spheres interacting with a repulsive Sutherland potential can be mapped onto the corresponding properties of hard-sphere (HS) systems, using effective diameters dependent on density and temperature [13,14]. More recently, Jackson and coworkers obtained an effective soft-repulsive potential based on the Mie model in order to reproduce structural properties of the HS system [15], a procedure that has been extended to square-well potentials [16] and applied successfully in molecular simulations of colloidal systems [17]. The approach of using potential models with soft repulsive and attractive interactions of variable range, such as the Mie model for chain molecules [18,19], have had important implications in the prediction of a wide variety of phase diagrams for molecular fluids [20].…”
Section: Introductionmentioning
confidence: 99%